Implementation of Responsibility Character Education Through Online Learning for Class 2 Elementary School Students: Implementasi Pendidikan karakter Tanggung Jawab Melalui Pembelajaran Daring Siswa Kelas II Sekolah Dasar - Kusianawati, Dhevy; Tirtoni, Feri (Universitas Muhammadiyah Sidoarjo, 2022)
Character education is very important to be instilled from an early age. Character education is the cultivation of values ​​to students to develop their potential and personality for the better. The purpose of this research is to implement responsible character education through online learning. This research was conducted because there is still a lack of students who are less responsible in collecting assignments, understanding the material especially in online learning situations. This research uses qualitative methods. The subjects in this study were primary and secondary. Collecting data in the form of observation, interviews, and documentation. The results showed that the implementation of the character of responsibility through online learning was good. although there are some obstacles in the collection of tasks. Therefore, the implementation of character education through online learning is very important because it is to develop the potential and personality of students for the better.